Towards a conceptualization of a social efficiency notion in management sciences - Grzeszczyk, Tadeusz A.; Pełszyński, Jacek (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: In the past, economic efficiency was a key criterion for assessing different types of activities undertaken by various organizations. It has been noticed that acquiring economic efficiency cannot be the only goal, and efficiency notion has many meanings. Processes and projects should be economically effective, at the same time being harmful to different social interests. There are difficulties in understanding and conceptualization of social efficiency notion in management sciences research, and, in particular, in the area of project management. Aim: This research aims to contribute to filling the gap concerning a conceptualization of a social efficiency notion in management sciences, with particular emphasis on the field of project management. Results: Achieving paper goal may simplify communication in the scientific community using the social efficiency concept, exchange of scientific information, further work related to operationalization of this concept and development methods for its measurement. Further work on social efficiency evaluation methods may facilitate considerations regarding the transition from the social efficiency notion phase to the concept phase and the idea of using social points for estimating obtained social effects. This opens the way for the development of more objective measurement principles and methods that do not require monetization of social impact, which is now commonly used e.g. in models like Social Return on Investment.